1998
DOI: 10.1046/j.1365-2699.1998.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographical links between steppe insects in the Monegros region (Aragón, NE Spain), the eastern Mediterranean, and central Asia

Abstract: Sixty‐two species of insects in thirty‐six families and nine orders, plus one species of Acari, were found to have disjunct distributions, or to belong to species groups with disjunct distributions, between the steppe areas in the central Monegros region (NE Spain) and the steppes in the eastern Mediterranean or central Asia. The accumulation of examples of a wide range of taxonomic groups, and the phyletic links of apparent endemic species of the central Ebro valley with eastern species, are considered to sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 50 publications
2
60
0
1
Order By: Relevance
“…hispanica . These two facts suggest more than one cycle of range expansion in the north and in the south, either during the Pliocene (5.3–2.6 Mya), when the emerged land in the south‐eastern and eastern Iberian Peninsula allowed the formation of a migration corridor between these areas (Martín et al ., ), and/or during the Pleistocene (2.6–0.01 Mya), when the increased climatic aridity during glaciations could have triggered a wider dispersal of the plants (Ribera & Blasco‐Zumeta, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hispanica . These two facts suggest more than one cycle of range expansion in the north and in the south, either during the Pliocene (5.3–2.6 Mya), when the emerged land in the south‐eastern and eastern Iberian Peninsula allowed the formation of a migration corridor between these areas (Martín et al ., ), and/or during the Pleistocene (2.6–0.01 Mya), when the increased climatic aridity during glaciations could have triggered a wider dispersal of the plants (Ribera & Blasco‐Zumeta, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of such cyclical climate changes on gypsophyte populations is still unclear. Some studies have shown that the northernmost Iberian gypsum outcrops in the Ebro valley were not directly affected by ice sheets (Ribera & Blasco‐Zumeta, ). However, global cooling during glaciations caused an increase in aridity in these territories, which could have favoured the expansion of drought‐adapted plants, such as gypsophytes, and facilitated the connectivity between previously isolated populations (Gornitz, ).…”
Section: Introductionmentioning
confidence: 99%
“…These figures indicate a stronger genetic depletion of the NE Spain populations as the result of a recent founder event with subsequent range expansion and/or an in situ bottleneck due to population size reduction with subsequent population growth. Furthermore, the NE Spain basin Tertiary flora and fauna apparently shows long continuity (Ribera & Blasco‐Zumeta 1998) and the low altitude of the Ebro valley range (< 700 m above sea level) precludes any past history of Quaternary ice sheet coverage. While most of the Iberian mountain and high‐plateau ranges have been regarded as potential glacial refugia for oreophyte and steppe taxa (Taberlet et al .…”
Section: Discussionmentioning
confidence: 99%
“…The estimate of droppings is even more important in our study if we consider that inland hypersaline habitats of M. wagneri are, by extension, shared by many macroinvertebrate species of great conservation interest within territories of high conservation concern. These include rare and fragmented taxa adapted to salinity, endemics dependent on salted soils, halophilous vegetation, or terrestrial steppic macroinvertebrates that find refuge from agriculture in these hypersaline ecosystems (Williams 1973, Ribera and Blasco-Zumeta 1998, Ribera 2000, Martín-Herrero et al 2003, Abellán et al 2005, Cordero et al 2007a, Cordero and Llorente 2008, Pichaco-García and Ramos 2016).…”
Section: Discussionmentioning
confidence: 99%